Жаңа технологиялар арқалы оқыўшылардың креатив раўажланыўын жетилистириўде экономикалық географияның орны - Абдираманов, Ж.Б (SCIENCE and SOCIETY, 2021)
The article reveals the importance of methods in the development of creative mumbling of secondary school students when teaching economic geography
Keywords: innovative methods; pedagogical technologies; creative thinking; pedagogical cooperation; training cases; entering a dia- logue